THE CHEMICAL COMPOSITION OF THE ACTIVE STARS - Glazunova, L. V. (Одеські астрономічні публікації, 2016)
The comparison of the results of the studies of the active stars’ chemical composition obtained by different authors has been performed. It was concluded that the difference between the abundances of some elements in active and inactive stars becomes significant (> 3σ) only for the active stars with high chromospheric activity (lgR’HK > -4). This is the case primarily for the light elements, namely Li, Na and Al, as well as heavy elements with Z > 30.